South‐western Atlantic reef fishes: Zoogeographical patterns and ecological drivers reveal a secondary biodiversity centre in the Atlantic Ocean. Issue 7 (2nd March 2018) - Pinheiro, Hudson T.; Rocha, Luiz A.; Macieira, Raphael M.; Carvalho‐Filho, Alfredo; Anderson, Antônio B.; Bender, Mariana G.; Di Dario, Fabio; Ferreira, Carlos Eduardo L.; Figueiredo‐Filho, Jessé; Francini‐Filho, Ronaldo; Gasparini, João L.; Joyeux, Jean‐Christophe; et al.
Abstract: Aim: To present an updated database of fish species recorded on south‐western Atlantic reef environments and to explore the ecological drivers of the structure, the latitudinal gradient of biodiversity and the centre of endemism in this peripheral province. Location: South‐western Atlantic (SWA): Brazilian and Argentinian Provinces. Methods: A database composed of 733 fish species along 23 locations in the SWA (00°55′ N to 43°00′ S) was compiled based on primary data, literature and museum records. Cluster and beta diversity analyses were carried out to evaluate faunal overlaps among locations and subprovinces. "Target‐area‐distance effect" and "stepping stones dispersal" hypotheses for assemblage composition were tested through Mantel tests. Relationships between the distribution patterns and ecological traits of reef fish species were investigated through generalized linear mixed‐effect models. Results: Out of the 733 fish species, 405 are SWA resident reef fishes, of which 111 (27%) are endemics and 78 are threatened with extinction. Cluster analysis detected six subprovinces in the SWA structured following the target‐area‐distance model, and with no evidence for a latitudinal gradient in diversity. The greatest overall richness and endemic species richness were found in the east–south‐eastern region. Depth range, habitat use and body size were the main drivers of SWA reef fish assemblage structure. Main conclusions: The Brazilian and Argentinian coasts constitute different provinces structured by oceanographic barriers and environmental filters. Similarities among oceanic islands indicate connectivity driven by stochastic and ecological factors. Species richness and endemism indicate that peripheral provinces may also bear centres of origin and biodiversity, patterns driven by parapatric/ecological speciation and the overlap between tropical and subtropical reef fish species. Ecological drivers of reef fish distribution, such as habitat specialization and body size, support hypotheses of speciation in the periphery. New approaches for spatial planning, marine protected areas and off‐reserve marine management are essential for the conservation and sustainability of SWA reef fishes.